Project Based Learning Based on Laboratory Experiments to Produce Laser Diffraction Experimental Devices on CD and DVD with 2 Measurement Methods - Swandi, Ahmad; Aprianto, Fahrizal; Rahmadhanningsih, Sri (Universitas Negeri Makassar, 2020)
All the CDs and DVDs that we find in the market have a large capacitance. This capacitance states how much storage capacity can be stored on the CD or DVD. Several studies have been conducted to determine or prove the capacitance of CDs and DVDs using laser light diffraction, but the measurement process is carried out conventionally, so the results obtained are less accurate. This research is an experimental study that aims to determine the capacitance of CDs and DVDs through red and green laser diffraction with the help of digital image measurements. To complete this research, the team followed the steps of Project Based Learning (PBL) which consisted of 7 stages, namely Challenging Problems or Questions, Sustained Inquiry, Authenticity, Student Voice and Choice, Reflection, Critique and Revision, and Public Product. By following the PBL stages, the team succeeded in producing an experimental device with good results. The results obtained with digital images are then compared with the results obtained conventionally to determine which measurements produce a more accurate value. Based on the results of the analysis, the conclusion is that measurements with digital images are better than using conventional measurements. From this process also, the team acquired more skills, namely critical thinking, problem solving, communication and collaboration.